LITERATUR REVIEW : THE EFFECT OF THIBBUN NABAWI (CUPPING THERAPY AND ACUPUNCTURE) ON REDUCING THE INTENSITY OF DYSMENORRHEA PAIN - K, Meilia Rahmawati; Rahmawati, Alfiah; Adhila, Nila Nur (LPPM Univ. Ibn Khaldun Bogor, 2023)
Menstruation is a process where the uterine lining decays. Menstruation often occurs during childbearing age, it is not uncommon for discomfort to be felt, one of which is dysmenorrhea . Dysmenorrhea is pain in the abdomen due to uterine cramps and menstrual blood disorders . Several therapies that can be used to reduce dysmenorrhea pain include pharmacological and non-pharmacological methods. Pharmacological therapy is taking ibuprofen, mefenamic acid and other drugs . However, giving pharmacological therapy can cause adverse side effects. Therefore, it can be pursued by using non-pharmacological treatment to minimize the occurrence of side effects. Thibbun nabawi is one of the methods of treatment that was sunnah by Rasulullah SAW. These methods include cupping therapy, and acupuncture The purpose of this study was to determine the effect of using Thibbun Nabawi, namely cupping and acupuncture on reducing the intensity of dysmenorrhea pain. This literature review was compiled by searching and collecting national and international research articles using a database Google schoolar , Pubmed, and Sciencedirect . The search was carried out using predetermined keywords and obtained 8 appropriate journals. From this study the results showed that there was an effect of using Thibun Nabawi (Cupping, and acupuncture) in reducing dysmenorrhea pain.